New perspectives for piezoelectric material-based cochlear implants: getting to nano - Danti, Serena; Berrettini, Stefano (Frontiers in Materials, 2024)
Sensorineural hearing loss (SNHL) occurs when the sound transduction mechanism in the inner ear is compromised, because of impairments affecting the sensory hair cellsthe actual biological transducers (90% of cases) -or the neurons, . which SNHL results in a broad spectrum of developmental, cognitive and psycho-social damages. To date, only cochlear implants (CIs) can offer a therapeutic solution to patients. They are multi-component electronic devices, surgically implanted, which capture, elaborate and convert the sound into electric stimuli delivered to the cochlea. Due to inherent limitations of the current electronic-based CIs, a new class of devices has been envisioned, which is based on piezoelectric materials. However, using piezoelectric membranes, the obtained sensitivity was not enough. The new frontiers for piezoelectric material-based CI aim at synergizing micro/nanofabrication aided by multiscale materials modeling with an in vivo tissue engineering approach to provide an implantable biomaterial-based system for SNHL, acting as a next generation CI. Specifically, the envisioned device will move forward the primitive concept of bulk-structured piezoelectric CIs by designing a nanostructured material (e.g., based on nanofibers) to be precisely delivered and be intimately and efficiently integrated with the cochlear microenvironment. Piezoelectric material-based CIs are indeed hypothesized to have a much higher resolution of electrical stimulation with more than hundreds of channels, compared to maximum 22 stimulating elements present in electronic-based CIs. Moreover, the stimulation site will be closest to peripheral nerve fiber endings for maximal resolution. This would be the first sensory implant with a feedback mechanism on a micrometer scale.